Locational Evocational and Emotional Topography in Anita Desai’s Fire on the Mountain, Clear Light of Day and Cry, the Peacock - Sanyal, Pritha (Integrated Journal for Research in Arts and Humanities, 2022)
The nature with all its phenomena governs the whole universe and it is a principal source for civilization to exist on this planet. This whole natural system cannot be controlled or governed by man. Though, being free gifts of nature, human beings stated misusing these resources for their personal gain and desires. As a result, natural resources are being degraded and gradually fading away the natural setting with the concern of the universal threats revolving around us. India is blessed with the wide range of natural resources, beginning from the Himalaya Regions to the dynamics of Sunderbans and the dry land-desert in Rajasthan. With the passing of time, these natural resources are harmed by population, pollution and other avarices of humankind. Now the writers come out with the global concerns for the degradation and depletion of nature and environmental landscapes. During the post- colonial era, Anita Desai is a leading Indian author in English who construct nature in their works. She remarkably writes on those aspects which she has observed. She succeeds in capturing and delineating the spirit of surroundings, places and social values. Nature has been known to reflect the inner state of human mind more than ever, either through as it is in its immediateness or by its phenomenal happenings like drizzle or heavy downpour. Griffin rightly interprets on it in her book, ‘Woman and Nature: Roaring Inside Her’, that “I know am made from the earth, as my mother’s hands were made from this earth, as her dreams came from this earth… you… are earth too, and listen as we speak to each other of what we know, the light is in us.” (Griffin 227) Based on this aspect Anita Desai’s masterpieces Fire on the Mountains and Clear Light of Day portray a beautiful significance of nature in every aspect of human nature. Set in the natural backdrop of Kasauli and Delhi respectively, these two novels aptly portray not only the isolation and loneliness haunting the human mind but also specifically demonstrates the passage of time in the life of people, connected by blood and the ups and downs in their relations, signified by their immediate surroundings and it's protection by Carson.